EVALUASI DAMPAK KEBIJAKAN PAS LINTAS BATAS DI KECAMATAN BADAU KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Kristoforus Orlando E.42008034 (FISIP Universitas Tanjungpura Pontianak, 2012)
The purpose of this research was to evaluate the impact of the agreement on the district of Badau, KapuasHulu regency west Borneo province.This research was qualitative research. The techniques in collecting data performed were interview,observation, and documentation. Activity in the data analysis carried out interactively and and runscontinuously until completion, so that data becomes saturated. Activity in the data analysis are data reduction,data display and conclusion drawing. The indicators used to evaluate the the impact of the agreement usingthe theory of William N. Dunn, the indicator's effectiveness, adequacy, equity, responsiveness and accuracy.The results showed that border pass policies had a positive impact and the negative impact on bordercommunities in the District Badau. The positive impact of the policy border pass are the ease of access to fulfilltheir daily needs, They can obtain better healthcare services in Malaysia than in Indonesia and it can deepenthe relationship between Indonesia and Malaysia residents who live in the border area. The negative impact ofborder pass are causing of illegal trade practices, wild collection practices, and can be a facility for illegallabor. Keywords: Evaluation, Policy, Impact, border pass.